2020
DOI: 10.1371/journal.pone.0240912
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive cardiac stress studies may not offer significant benefit in pre-kidney transplant evaluation: A retrospective cohort study

Abstract: Background Screening with cardiac non-invasive stress studies (NISS) prior to listing for kidney transplantation can help in identifying treatable coronary disease and is considered an integral part of pre-kidney transplant evaluation. However, few studies assessed their effectiveness in all patients evaluated for transplantation in clinical practice. To evaluate the role of NISS in pre-kidney transplant evaluation we analyzed their impact prior to waitlisting in 1053 adult CKD-5 patients consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
(40 reference statements)
0
12
0
Order By: Relevance
“… 33 Cardiac testing‚ while perhaps important for risk stratification‚ may not lead to therapeutic interventions that enhance survival and has been shown to delay the transplant evaluation process. 34 Simultaneously, there is growing appreciation for the value of functional or frailty assessments during candidate selection as important prognosticators of transplant and waitlist outcomes. Serially measuring BNP at the time of transplant re-evaluation may augment the cardiac re-evaluation process in transplant.…”
Section: Discussionmentioning
confidence: 99%
“… 33 Cardiac testing‚ while perhaps important for risk stratification‚ may not lead to therapeutic interventions that enhance survival and has been shown to delay the transplant evaluation process. 34 Simultaneously, there is growing appreciation for the value of functional or frailty assessments during candidate selection as important prognosticators of transplant and waitlist outcomes. Serially measuring BNP at the time of transplant re-evaluation may augment the cardiac re-evaluation process in transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Data were not available for those who were screened and not listed due to an abnormal screening test, or listed but not transplanted due to MACE that occurred on the waitlist. Screening results are just one factor in a complex assessment of patients for transplantation, with the proportion of patients excluded due to cardiac screening abnormalities estimated at 1%–4% ( 71 , 72 , 73 ). In a target trial examining whether cardiac screening improves post-transplant outcomes these data would ideally be known, and neither PS or IV techniques specifically address this issue.…”
Section: Does Screening For Coronary Artery Disease Reduce Post-trans...mentioning
confidence: 99%
“…Although there are no other RCTs examining whether more screening for asymptomatic coronary artery disease in prospective KTR improves survival or reduces CV events after transplantation, two important observational studies have reported recently. An intensive CV risk stratification protocol implemented nationwide in Austria in 2007 resulted in over 50% of transplanted patients having a coronary angiogram but failed to demonstrate any improvement in patient survival or a reduction in coronary events in patients transplanted directly after (2008–11) or 5 years after (2012–15) compared with historical data (2003–07) [ 31 , 33 ]. A prospective study of 2572 UK KTR who received a transplant in 2011–17 in 18 centres found that 51% underwent cardiac screening pre-transplantation with screening by centre varying from 5% to 100% [ 32 ].…”
Section: Value Of Revascularization In Stable Ischaemic Heart Diseasementioning
confidence: 99%
“…The very considerable differences in screening practices both within [ 33 ] and between countries raise concern about whether patients in many centres are being denied access to a kidney transplant without supportive evidence while patients with similar characteristics in other centres are wait-listed promptly [ 75 ]. In the UK, a recent study found that the proportion of KTRs that had undergone CV screening with either a stress test or coronary angiogram ranged between 5% and 100% [ 33 ]. An important and uncomfortable question is raised: how many patients in the centres with high screening rates were, potentially unnecessarily, denied access to transplantation [ 76 ]?…”
Section: Evidence That Conventional Approach To Cardiac Screening Causes Harmmentioning
confidence: 99%